Porous silicon material and method for producing the same, as well as a negative electrode active material having a porous silicon material, a composition for a secondary battery negative electrode, a secondary battery negative electrode and secondary battery
Patent Information
- Application Number
- JP2025062213
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0010】 本発明によれば、充放電の繰返しに伴う膨張や収縮が抑制され、初回放電容量及びサイクル特性に優れる負極を作成できる、負極活物質として有用な多孔質シリコン材料及びその製造方法を提供できる。また、本発明によれば、かかる多孔質シリコン材料を含有する負極活物質、及びかかる負極活物質を有する、充放電特性等の電池特性に優れる二次電池を提供できる。
Smart Images

Figure 2026168789000001 
Figure 2026168789000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a porous silicon material and a method for producing the same, as well as a negative electrode active material having the porous silicon material, a composition for a secondary battery negative electrode, a secondary battery negative electrode, and a secondary battery. More specifically, the present invention relates to a porous silicon material suitably applicable as a negative electrode active material for a secondary battery, a method for producing the same, and a secondary battery containing the porous silicon material as a negative electrode. [Background technology]
[0002] In recent years, with the advancement of high performance and miniaturization in various portable electronic and communication devices, the demand for small, high-capacity secondary batteries has been increasing. In particular, various lithium-ion batteries, which are non-aqueous electrolyte secondary batteries that use lithium intercalation compounds as the negative electrode active material, capable of intercalating and releasing lithium ions between crystal planes during charging and discharging, are rapidly being deployed in hybrid vehicles, electric vehicles, and home energy storage systems, and their range of applications is expanding. Therefore, there is a need for lithium-ion batteries with even higher capacity and further improved battery characteristics such as cycle characteristics and discharge rate characteristics. Conventional lithium-ion batteries primarily use graphite as the negative electrode material. However, graphite has a low theoretical capacity density (372 mAh / g), which limits the development of lithium-ion batteries with even higher energy densities. To compensate for the limited theoretical capacity density of graphite, negative electrode materials using elements capable of intercalating and releasing lithium ions, such as silicon (Si), metals like tin, or alloys and oxides of other elements, are being investigated. Among these, silicon has a theoretical capacity more than 10 times that of graphite (4200 mAh / g), making silicon and silicon-containing negative electrode active materials noteworthy as next-generation negative electrode materials capable of achieving higher capacity.
[0003] However, silicon and silicon-containing negative electrode active materials undergo significant volume expansion and contraction with the intercalation and release of lithium ions. Repeated charging and discharging causes the active material to be pulverized, leading to delamination and disintegration of the electrode material and deterioration of electronic conductivity, thus resulting in poor charge-discharge cycle characteristics. As one attempt to improve the charge-discharge cycle characteristics and expansion characteristics of silicon-containing negative electrode active materials, the development of porous silicon materials is underway. Patent Document 1 discloses a negative electrode active material containing porous silicon particles, preferably obtained by an electrochemical etching method, in which a specific 50% particle size, and furthermore, the difference between the 90% particle size and the 10% particle size, is within a specific range, and the surface may be coated with a conductive agent, and which is said to have excellent cycle characteristics and output characteristics.
[0004] Furthermore, there is growing interest in techniques for creating porous silicon materials by preparing alloys of silicon with metal elements that form a eutectic composition, and then using de-alloying reactions with acids or alkalis. For example, Patent Document 2 discloses a method for producing porous silicon particles, comprising the step of atomizing a silicon alloy containing 50% or more by mass of aluminum (Al) and 50% or less by mass of silicon (Si), and then removing the Al. Preferably, a silicon alloy in which the Al and Si are in a blending ratio near the eutectic composition can be used to obtain porous silicon particles containing a three-dimensional network structure of silicon with voids, and having an average porosity of 50% by volume or more and 95% by volume or less. It is said that an all-solid-state lithium-ion secondary battery having a negative electrode containing such porous silicon particles as a negative electrode active material can suppress the deterioration of charge-discharge characteristics (cycle characteristics). Patent Document 3 discloses porous amorphous silicon having a lamellar structure or columnar structure with an average particle size or average column diameter within a specific range, and an average porosity of 10 to 99%, which is said to improve battery performance such as charge / discharge efficiency and battery capacity when used as a negative electrode material. Patent Document 4 discloses a method for preparing a silicon alloy from a raw material containing 5 atom% to 15 atom% titanium (Ti), 10 atom% to 50 atom% Al, and the remainder being Si, and then removing the Al contained in the alloy to obtain a porous silicon material. When used in energy storage devices such as lithium-ion batteries, this material is said to mitigate volume expansion and contraction and improve cycle characteristics. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2016-51622 [Patent Document 2] Japanese Patent Publication No. 2021-123517 [Patent Document 3] International Publication No. 2020 / 194794 [Patent Document 4] Japanese Patent Publication No. 2023-068494 [Overview of the project] [Problems that the invention aims to solve]
[0006] While Patent Document 1 specifies the distribution of the average particle size of the porous silicon particles, it does not disclose any details regarding the porosity of the "pores" that contribute to improving charge-discharge characteristics by suppressing degradation due to the expansion and contraction of silicon (Si). Furthermore, the electrochemical etching method (in other words, the anodic oxidation method) and ultrasonic crushing method mentioned as methods for obtaining porous silicon particles are difficult to mass-produce from an industrial standpoint and have challenges in terms of productivity. The porous silicon particles disclosed in Patent Document 2 are obtained using a silicon alloy in which Al and Si are in a composition ratio near the eutectic composition, while the porous amorphous silicon disclosed in Patent Document 3 is formed by cooling a molten metal containing metal and silicon, specifically a molten metal containing aluminum and silicon, at a predetermined cooling rate to form a eutectic alloy, and then selectively dissolving the metal from this eutectic alloy. In Patent Document 3, it is stated that the aluminum-silicon alloy preferably contains silicon (Si) at an atomic percentage of 1 to 50%, thereby enabling the production of porous amorphous silicon with an average porosity of 50 to 99%, but in reality, only an example using a eutectic alloy with an Al / Si = 88 / 12 (atom%) composition is shown. Furthermore, the three-component alloys exemplified as other raw materials are also eutectic alloys. Thus, using a silicon alloy with a eutectic composition as a raw material limits the Si content, resulting in high production costs for porous silicon particles when calculated on a silicon-only basis, posing challenges from a productivity standpoint. On the other hand, increasing the Si composition in silicon alloys usually leads to increased Si segregation, which can cause problems such as expansion and a decrease in cycle properties. The porous silicon material obtained by the method disclosed in Patent Document 4 still presents challenges in suppressing expansion, as Si precipitation occurs and TiSi2 tends to be present inside the particles. Therefore, there is still a need for a silicon-based anode active material that can be manufactured economically, has high capacity, improves battery characteristics such as cycle performance, and suppresses expansion and contraction during charging and discharging.
[0007] The inventors investigated the composition of the silicon alloy used as the raw material in order to improve the mass production of porous silicon materials. They found that when an aluminum-silicon alloy (Al-Si alloy) with a non-eutectic composition and a high Si composition ratio is used as the raw material, dendritic or massive Si crystals precipitate irregularly in the silicon phase of the resulting silicon material, i.e., Si segregation (blocking) is observed, and the porous portion decreases. In this case, because the porous portion is small and rough, there is less relaxation phase associated with the expansion and contraction of Si, and structural failure in the segregated portion of the silicon phase is likely to be significant, so it is presumed that the battery characteristics will not be fully realized. To resolve this phenomenon, the inventors conducted further investigations and found that by incorporating a specific amount of titanium (Ti) into a non-eutectic Al-Si alloy with a higher Si composition ratio, silicon (Si) segregation can be suppressed. Furthermore, they found that, preferably, adding aluminum metal after preparing a Si-Ti alloy to obtain an Al-Si-Ti alloy significantly suppresses Si segregation. They then discovered that by using a porous silicon material obtained by eluting Al and Ti from alloy particles obtained by atomizing an Al-Si-Ti alloy containing a specific amount of Ti using a gas atomizer, expansion and contraction associated with repeated charging and discharging are suppressed, and a negative electrode with excellent initial discharge capacity and cycle characteristics can be mass-produced, thus completing the present invention.
[0008] The object of the present invention is to provide a porous silicon material useful as a negative electrode active material and a method for producing the same, which can create a negative electrode that suppresses expansion and contraction associated with repeated charging and discharging and exhibits excellent initial discharge capacity and cycle characteristics. Another object of the present invention is to provide a negative electrode active material containing such porous silicon material, and a secondary battery having such negative electrode active material. [Means for solving the problem]
[0009] The present invention has the following aspects. [1] A porous silicon material having a lamellar or columnar structure with an average column diameter of 1 nm to 100 nm in silicon domains, and a porosity Q calculated by the following formula (1) being greater than 40% and less than 80%. Q(%) = 100 × P / (V + P) ... (1) P: Pore volume of porous silicon material V: Volume of porous silicon material [2] A porous silicon material of [1] comprising at least a portion of an amorphous silicon component. [3] A porous silicon material according to [1] or [2], wherein the elemental mass ratio of silicon (Si) to oxygen (O) (O / Si) is A, and the BET specific surface area measured by nitrogen gas adsorption is B, and the value Y calculated by the following formula (2) is greater than 0 and less than 0.2. Y=100×A / B ···(2) [4] The porous silicon material according to any one of [1] to [3], which has one or more crystallization peaks at 350°C or higher and 450°C or lower in DSC (differential scanning calorimetry) analysis. [5] The porous silicon material according to any one of [1] to [4], wherein the crystallite size of the Si(111) plane calculated by the fundamental parameter (FP) method based on X-ray diffraction analysis is 130 nm or less. [6] The porous silicon material according to any one of [1] to [5], which is formed using an alloy represented by the following formula (3) as a raw material. Al x Si y Ti z ···(3) (wherein, x is 45 atom% or more and less than 75 atom%, y is 25 atom% or more and 45 atom% or less, and z is more than 0 atom% and less than 5 atom%. ) [7] The porous silicon material according to [6], wherein the element mass ratio E of the Si to the Al is more than 0 and less than 0.04. [8] The porous silicon material according to [6] or [7], which does not contain an Al-Si-Ti compound. [9] A method for producing the porous silicon material according to any one of [1] to [8], comprising the following steps. (i) A step of producing a Si-Ti alloy (ii) A step of adding aluminum metal to the Si-Ti alloy obtained in the step (i) to produce an alloy represented by the following formula (3) Al x Si y Ti z ···(3) (wherein, x is 45 atom% or more and less than 75 atom%, y is 25 atom% or more and 45 atom% or less, and z is more than 0 atom% and less than 5 atom%. ) (iii) A step of granulating the alloy represented by the formula (3) obtained in the step (ii) with a gas atomization apparatus to obtain alloy particles (iv) A step of subjecting the alloy particles obtained in the step (iii) to dealloying with an acid or alkali containing alcohol to obtain a porous silicon material
[10] A method for producing the porous silicon material according to [9], wherein the average particle size (D50) of the alloy particles obtained in step (iii) is in the range of more than 0.1 μm and less than 20 μm.
[11] A negative electrode active material comprising any of the porous silicon materials [1] to [8]. A composition for the negative electrode of a secondary battery, containing the negative electrode active material of
[12]
[11] . A secondary battery negative electrode comprising a negative electrode material layer formed using the secondary battery negative electrode composition of
[13]
[12] . A secondary battery comprising a negative electrode, a positive electrode, an electrolyte, and a separator, as described in
[14]
[13] . [Effects of the Invention]
[0010] According to the present invention, a porous silicon material useful as a negative electrode active material and a method for producing the same can be provided, which can create a negative electrode that suppresses expansion and contraction associated with repeated charging and discharging and has excellent initial discharge capacity and cycle characteristics. Furthermore, according to the present invention, a negative electrode active material containing such porous silicon material and a secondary battery having such a negative electrode active material that has excellent battery characteristics such as charge-discharge characteristics can be provided. [Modes for carrying out the invention]
[0011] <Porous Silicone Material> The porous silicon material of the present invention has a lamellar structure or columnar structure in which the average pillar diameter of the silicon domains is 1 nm to 100 nm, and the porosity Q calculated by the following formula (1) is greater than 40% and less than 80%. Q(%) = 100 × P / (V + P) ... (1) P: Pore volume of porous silicon material V: Volume of porous silicon material In other words, the silicon domains in the porous silicon material of the present invention preferably have a lamellar structure in which the spacing between adjacent lamellae is 1 nm to 100 nm, or a columnar structure in which the spacing between adjacent pillars is 1 nm to 100 nm. Furthermore, the porosity Q calculated by formula (1) of the porous silicon material of the present invention is preferably 45% or more, and more preferably 50% or more. Moreover, such porosity Q is preferably 75% or less, and more preferably 70% or less. Because the porosity Q of the porous silicon material of the present invention is within the aforementioned range, the volume expansion associated with alloying silicon and lithium during charging can be sufficiently buffered, and volume changes can be suppressed. Furthermore, the strength of the porous silicon material of the present invention is less likely to decrease, and pulverization due to volume changes can be prevented. Therefore, the expansion of the negative electrode containing the porous silicon material of the present invention is suppressed, and the battery characteristics of a secondary battery equipped with such a negative electrode are improved.
[0012] Here, the porosity in Patent Document 3 is the atomic percentage content of the component selectively eluted from the eutectic metal in the eutectic metal, and is different from the porosity Q calculated by formula (1) above. For example, if all components other than silicon (Si) are leached from a eutectic metal, the porosity in Patent Document 3 is calculated as the atomic percentage content (%) of the components leached from the eutectic metal in the eutectic metal [porosity (%) = 100 - atomic percentage content of Si in the eutectic metal]. In other words, the porosity is approximated by the content of metals other than Si, and the porosity when using an Al-Si eutectic alloy is 88%. On the other hand, the Si content of the alloy shown in formula (3), which is suitably used as a raw material for the porous silicon material of the present invention, is 25 atom% to 45 atom%. Being within this range increases the Si content of the porous silicon material of the present invention and strengthens its structure. In the present invention, as shown in formula (1) above, the porosity is calculated from the pore volume and material volume of the obtained porous silicon material. When the porosity of the obtained porous silicon material is determined by the calculation method in Patent Document 3, it is 55 to 75%.
[0013] The porous silicon material of the present invention preferably contains at least a portion of amorphous silicon components. The proportion of amorphous silicon components in the entire silicon phase of the porous silicon material of the present invention is preferably in the range of 10% to 60%. When the porous silicon material of the present invention contains at least a portion of amorphous silicon, the amorphous silicon portion readily alloys with lithium during charging and readily releases lithium during discharging. Furthermore, the amorphous silicon portion lacks dislocation defects and grain boundaries, resulting in uniform stress distribution under mechanical stress loads. Therefore, compared to the crystalline silicon portion, it exhibits higher strength and elasticity, and the volume expansion during silicon alloying with lithium is easily suppressed, making it less prone to pulverization. Consequently, battery characteristics such as cycle characteristics of a secondary battery equipped with a negative electrode containing the porous silicon material of the present invention are easily improved.
[0014] In the porous silicon material of the present invention, when the elemental mass ratio of silicon (Si) to oxygen (O) (O / Si) is A and the BET specific surface area measured by nitrogen gas adsorption is B, it is preferable that the value Y calculated by the following formula (2) is greater than 0 and less than 0.2. Y = 100 × A / B ... (2) The value Y is an index representing the degree of oxidation of the surface of the porous silicon material. When the value Y is within the aforementioned range, the surface of the porous silicon material tends to have a continuous three-dimensional network structure of Si, making alloying and de-alloying with lithium easier. Therefore, battery characteristics such as cycle characteristics of a secondary battery equipped with a negative electrode containing the porous silicon material of the present invention tend to improve. In addition, because the degree of oxidation of the surface is low, i.e., there is little silicon oxide on the surface, the decrease in initial charge-discharge efficiency due to irreversibility caused by reaction with lithium ions supplied from the positive electrode during the first charge is easily suppressed. The value Y can be suitably controlled by controlling step (iii) in the method for producing the porous silicon material of the present invention, which will be described later, namely by controlling the temperature, gas pressure, cooling rate, etc. when atomizing in an atomizing device, and by controlling step (iv) namely the temperature, processing time when de-alloying with an acid or alkali containing alcohol, as well as the conditions for washing with alcohol.
[0015] The porous silicon material of the present invention preferably has one or more crystallization peaks between 350°C and 450°C in DSC (Differential Scanning Calorimetry) analysis. When the porous silicon material of the present invention has the aforementioned crystallization peaks, it serves as evidence that the porous silicon material of the present invention contains amorphous silicon components, and the above-mentioned effects are more likely to be achieved. Furthermore, the porous silicon material of the present invention preferably has one or more crystallization peaks between 350°C and 450°C in DSC analysis, and more preferably has a heat of crystallization of 20 mW / g or more determined from the crystallization peaks. It is even more preferable that the heat of crystallization is 25 mW / g or more. It is preferable that the heat of crystallization is 100 mW / g or less. The porous silicon material of the present invention, in which the heat of crystallization determined from the crystallization peaks is within the above range, is industrially advantageous and easy to manufacture.
[0016] The porous silicon material of the present invention preferably has a Si(111) plane crystallite size of 130 nm or less, and more preferably 100 nm or less, as calculated by the fundamental parameter (FP) method using X-ray diffraction analysis. A crystallite size of 5 nm or more is preferable. A Si(111) plane crystallite size within the above range is preferable from the viewpoint of battery characteristics such as capacity and cycle characteristics when used as a secondary battery. The porous silicon material of the present invention is preferably formed from an alloy represented by formula (3), described later, and by incorporating a specific amount of titanium (Ti) into a non-eutectic Al-Si alloy with a high Si composition ratio, Si segregation can be suppressed, making it easier to control the Si(111) plane crystallite size within the above range. Furthermore, the ability to control the Si(111) plane crystallite size makes it easier to control the temperature range in which the crystallization peak appears in the DSC analysis described above, and to control the average pillar diameter of the silicon domains to a specific structure. The details of the X-ray diffraction analysis are as described in the examples below.
[0017] The porous silicon material of the present invention is preferably formed using the alloy shown in formula (3) below as a raw material. Al x Si y Tiz ...(3) (In the formula, x is 45 atom% or more and less than 75 atom%, y is 25 atom% or more and 45 atom% or less, and z is more than 0 atom% and less than 5 atom%.) The above x is preferably 50 atom% or more, more preferably 55 atom% or more. x is preferably 72.5 atom% or less, more preferably 70 atom% or less. The above y is preferably 27.5 atom% or more, more preferably 30 atom% or more. y is preferably 42.5 atom% or less, more preferably 40 atom% or less. The above z is preferably 0.05 atom% or more, more preferably 0.1 atom% or more. z is preferably 4.5 atom% or less, more preferably 4 atom% or less.
[0018] When the porous silicon material of the present invention is formed using the alloy represented by formula (3) as a raw material, the elemental mass ratio E of Si to Al is preferably more than 0 and less than 0.04. Such elemental mass ratio E means the atom% of Al relative to the atom% of Si (that is, Al / Si). In other words, the porous silicon material of the present invention preferably contains almost no Al.
[0019] Further, when the porous silicon material of the present invention is formed using the alloy represented by formula (3) as a raw material, it preferably does not contain an Al-Si-Ti compound. Here, the alloy represented by formula (3) substantially includes bonds such as Al-Al, Si-Si, Ti-Si, Al-Si, Al-Ti, Si-Ti, and Al-Si-Ti, and is a generic term for these, and the Al-Si-Ti compound refers to those having an Al-Si-Ti intermetallic bond among them. In other words, the porous silicon material of the present invention preferably does not contain a compound composed of an Al-Si-Ti intermetallic bond. In this specification, "does not contain Al-Si-Ti compounds" means that no peaks originating from intermetallic compounds consisting of Al-Si-Ti bonds are observed by X-ray diffraction (XRD), that is, compounds consisting of Al-Si-Ti intermetallic bonds do not exist.
[0020] The average particle size (D50) of the porous silicon material of the present invention is preferably in the range of more than 0.1 μm and less than 20 μm, and more preferably in the range of 0.2 μm to 15 μm. When the D50 of the porous silicon material of the present invention is within the above range, the capacity and cycle characteristics when used as a secondary battery are more easily improved, and expansion and contraction are more easily suppressed.
[0021] <Method for manufacturing porous silicon material> The porous silicon material of the present invention can preferably be manufactured by a manufacturing method comprising the following steps. (i) Process for manufacturing Si-Ti alloy (ii) A step of adding aluminum metal to the Si-Ti alloy obtained in step (i) above to produce an alloy represented by the following formula (3). Al x Si y Ti z ...(3) (In the formula, x is between 45 atom% and less than 75 atom%; y is between 25 atom% and 45 atom%; and z is greater than 0 atom% and less than 5 atom%.) (iii) A step of atomizing the alloy represented by formula (3) obtained in step (ii) using a gas atomizer to obtain alloy particles. (iv) A step of obtaining a porous silicon material by dealloying the alloy particles obtained in step (iii) with an acid or alkali containing alcohol.
[0022] [Process (i) and Process (ii)] A Si-Ti alloy is prepared by melting silicon and titanium in an inert gas atmosphere such as argon, using a melting method such as an arc melting furnace. Then, aluminum metal is added to the same furnace and melted to obtain the alloy shown in formula (3). The preferred ranges of atom% represented by x, y, and z in formula (3) are as described above. The silicon, titanium, and aluminum used as raw materials may contain small amounts of impurities such as Fe, C, Cu, Ni, and P that inevitably remain during their refining, but it is preferable that the impurity content be as low as possible. For example, when the total amount of Si, Ti, and Al is 100 atom%, it is preferable that the impurity content be 2 atom% or less, and more preferably 1.5 atom% or less.
[0023] [Step (iii)] The alloy represented by formula (3) above is used as molten metal and atomized in a gas atomizer to obtain alloy particles. The cooling rate during atomization in the gas atomizer is 10 2 Preferably it is k / second or higher, 10 6 A cooling rate of 10 K / sec or higher is more preferable. 8 A pressure of K / sec or less is preferred. Furthermore, when the alloy represented by formula (3) is molten, it is preferable to do so under an inert gas atmosphere such as nitrogen, helium, or argon, and more preferably under a helium or argon atmosphere. In addition, atomization using a gas atomizer is preferably carried out under a helium or argon atmosphere. By controlling the cooling rate within the aforementioned range, the crystalline phase of the Si component in the resulting alloy particles does not become excessively enlarged, making it easier to control the domain size to 1 nm to 100 nm, and also making it easier for at least a portion of the silicon phase to contain amorphous silicon components. Furthermore, the domain size of the metallic phase (aluminum-based phase) in the alloy particles can be controlled to 1 nm to 100 nm. In this case, it is possible to manufacture a porous silicon material having a lamellar structure in which the spacing between adjacent lamellae is 1 nm to 100 nm, or a columnar structure in which the spacing between adjacent pillars is 1 nm to 100 nm. Furthermore, steps (i) to (iii) make it easier to obtain alloy particles with a low or no content of Al-Si-Ti compounds having Al-Si-Ti intermetallic bonds, and thus make it easier to manufacture the porous silicon material of the present invention that does not contain Al-Si-Ti compounds, which is preferable.
[0024] It is empirically known that when Si-Ti alloys are produced by adding titanium to molten silicon, segregation of Si due to the crystallization of primary Si can be suppressed, and the presence of SiTi2 as an intermetallic compound is presumed to be the reason for this. In steps (i) and (ii) described above, it is thought that cluster-like structures related to SiTi2 are likely to be formed. Furthermore, liquids with compositions that form intermetallic compounds generally tend to have increasing viscosity. In step (iii) described above, i.e., the rapid cooling process in which the alloy shown in equation (3) is atomized using a gas atomizer, it is presumed that a cluster-like structure related to SiTi2 is formed in the molten metal, increasing viscosity and preventing the aggregation of Si atoms, thereby suppressing the crystallization of primary Si (segregation of Si). In other words, the degree of supercooling of the liquid Al-Si alloy in the rapid cooling process increases, and it is thought that the crystalline phase and metallic phase of the Si component in the alloy particles are more easily refined as described above.
[0025] The average particle size (D50) of the alloy particles is preferably in the range of greater than 0.1 μm and less than 20 μm. More preferably, the D50 of the alloy particles is between 0.2 μm and 18 μm, and even more preferably between 0.3 μm and 15 μm. Furthermore, it is preferable that the alloy particles have a spherical shape. When the D50 of the alloy particles is within the aforementioned range and is spherical, it becomes easier to maintain the strength of the particles of the porous silicon material of the present invention obtained from such alloy particles, and it also becomes easier to suppress volume changes of the porous silicon material itself during charging and discharging. As a result, the electrical properties such as the cycle characteristics of a secondary battery equipped with a negative electrode containing the porous silicon material of the present invention tend to improve. Since the D50 of the alloy particles becomes the D50 of the resulting porous silicon material, it is preferable to adjust the average particle size of the alloy particles to a range of more than 0.1 μm and less than 20 μm. The D50 of the alloy particles and the porous silicon material of the present invention is the particle size (D50) at which the cumulative volume distribution curve reaches 50% when plotted from the smallest diameter side, based on the particle size distribution measured by dynamic light scattering using a laser diffraction particle size analyzer or the like. As described in the examples below, the measurement was performed using a laser diffraction particle size analyzer (Malvern Panalytical, "Mastersizer 3000").
[0026] In this invention, the specific alloy represented by formula (3) is atomized using a gas atomizer, rather than a single-roll liquid quenching method using a single-roll casting machine or a water atomizer. Therefore, it is easier to obtain spherical alloy particles in which D50 is within the aforementioned range. With the single-roll liquid quenching method, a thin strip of quenched alloy is obtained, which requires further pulverization into a powder.
[0027] [Step (iv)] By de-alloying these alloy particles with an alcohol-containing acid or alkali, the porous silicon material of the present invention, having a lamellar structure or columnar structure with an average particle size or average column diameter of 1 nm to 100 nm, can be produced. The acid or alkali is preferably one that dissolves elements and / or compounds other than Si in the alloy particles without dissolving Si, and examples include hydrochloric acid, sulfuric acid, sodium hydroxide, potassium hydroxide, etc. The acid or alkali is preferably used as an aqueous solution. When used as an aqueous solution, the concentration of the acid or alkali is not particularly limited as long as it is within the range that can dissolve elements and / or compounds other than Si in the alloy particles, and can be, for example, in the range of 1 to 5 mol / L.
[0028] Step (iv) is characterized in that the aqueous solution of the acid or alkali contains an alcohol. The alcohol is preferably a water-miscible alcohol with a boiling point of 100°C or less at atmospheric pressure, such as methanol, ethanol, n-propanol, isopropanol, or other aliphatic monoalcohols having 1 to 3 carbon atoms. There are no particular restrictions on the alcohol content in an aqueous solution of an acid or alkali, but it is preferably in the range of 0.1% to 30% by mass relative to the total volume of the aqueous solution, and more preferably in the range of 0.5% to 20% by mass. De-alloying the alloy particles obtained in step (iii) using an aqueous solution of an acid or alkali containing the aforementioned alcohol within the aforementioned range is preferable from the viewpoint of increasing the rate of de-alloying and easily suppressing surface oxidation.
[0029] Dealloying can be carried out, for example, by immersing alloy particles in an acid or alkali solution containing alcohol, heating it to room temperature (25°C) or 30°C to 60°C, and stirring or letting it stand for 1 to 24 hours. The hydrophilic groups of alcohol make it easier for the acid or alkali to adhere to the surface of the alloy particles, thus promoting dealloying in an industrially advantageous manner. The resulting porous silicon material is preferably further washed and dried. In particular, it is preferable to obtain the porous silicon material of the present invention by cleaning with alcohol after de-alloying. Examples of alcohols used for such cleaning include those similar to the alcohols mentioned above that are contained in aqueous solutions of acids or alkalis. The alcohol used for cleaning is preferably dehydrated. In other words, the alcohol used to clean the porous silicon material obtained by dealloying preferably has a water content of 10% by mass or less, and more preferably 5% by mass or less. By cleaning the porous silicon material obtained by dealloying with dehydrated alcohol, it is easier to suppress the formation of excessive oxide films on the surface of the porous silicon material. In other words, it is easier to control the aforementioned value Y within the aforementioned range. Drying can be carried out using known dryers, vacuum dryers, etc., at a temperature range of, for example, 25 to 200°C, under an inert gas atmosphere, at atmospheric pressure, or under reduced pressure conditions, for a period of 1 minute to 24 hours.
[0030] The porous silicon material of the present invention obtained as described above has voids that can mitigate volume changes associated with the expansion and contraction of Si during charging and discharging. Therefore, expansion can be suppressed in the negative electrode of a secondary battery containing the porous silicon material of the present invention, and the pulverization of the porous silicon material can be suppressed. In particular, Si segregation (Si precipitation) that occurs when the Si composition ratio is increased compared to the eutectic composition of Al and Si in the raw material alloy can be improved by adding a specific amount of titanium (Ti) in the order described above to produce an alloy represented by formula (3) (Al-Si-Ti alloy). Furthermore, by atomizing the alloy represented by formula (3) using a gas atomizing device, spherical alloy particles with D50 within the aforementioned range can be easily obtained, and as described above, de-alloying with an acid or alkali containing alcohol clearly improves the cycle characteristics and expansion characteristics. Furthermore, even when the Si composition ratio is increased, the presence of amorphous silicon components in at least a portion of the silicon phase suppresses expansion and further improves cycle characteristics. Furthermore, even with Al-Si alloys with a non-eutectic composition and a high Si content, by incorporating titanium within a specific range in the alloy represented by formula (3), a silicon material with a high proportion of porous material and the porosity defined in this invention can be obtained. In other words, since the alloy of formula (3), which has a higher silicon content than the eutectic composition of silicon and aluminum, can be used as a raw material, mass production is improved and it is economically advantageous.
[0031] <Negative electrode active material, secondary battery negative electrode composition, secondary battery negative electrode, secondary battery> The present invention encompasses a negative electrode active material (hereinafter also referred to as "this negative electrode active material") containing the porous silicon material of the present invention described above. This negative electrode active material may also contain active materials other than the porous silicon material of the present invention, such as carbonaceous materials. It may also contain other necessary third components. The negative electrode active material may have its surface coated with a coating material. The coating material is preferably a substance that is expected to have electronic conductivity, lithium ion conductivity, and an effect of suppressing the decomposition of the electrolyte, and examples of electronically conductive substances include carbon, titanium, and nickel.
[0032] The present invention also includes a secondary battery negative electrode composition containing the negative electrode active material, and a secondary battery negative electrode comprising a negative electrode material layer formed using such secondary battery negative electrode composition. The present invention further includes a secondary battery comprising the above-mentioned negative electrode, positive electrode, electrolyte, and separator.
[0033] This negative electrode active material exhibits excellent capacity and cycle characteristics, and furthermore, expansion and contraction during charging and discharging are suppressed. Therefore, secondary batteries containing this negative electrode active material, and more specifically secondary batteries having a negative electrode comprising a negative electrode material layer containing this negative electrode active material, exhibit good charge-discharge characteristics and excellent cycle characteristics. For example, the negative electrode active material and an organic binder are kneaded together with a solvent using a dispersion device such as a stirrer, ball mill, super sand mill, or pressurized kneader to prepare a negative electrode composition for secondary batteries. This negative electrode composition for secondary batteries can be applied to a current collector (e.g., copper foil) to form a negative electrode layer. The solvent is preferably one that does not react with the porous silicon material of the present invention, and examples include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, and cyclohexanone; alcohols such as ethanol, methanol, n-propanol, isopropanol, benzyl alcohol, and diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as hexane, cyclohexane, octane, and nonane; ethers such as tetrahydrofuran, diethyl ether, and glyme; and esters such as ethyl acetate and butyl acetate. When preparing a composition for the negative electrode of a secondary battery, if necessary, high-molecular-weight non-aqueous dispersants such as polyethers, polyalkylene polyamines, and polycarboxylic acid partial alkyl esters; low-molecular-weight non-aqueous dispersants such as polyhydric alcohol esters and alkyl polyamines; and dispersants such as polyphosphates may be included in the presence of these materials.
[0034] Examples of the organic binders include styrene-butadiene rubber copolymers (hereinafter also referred to as "SBR"); ethylenically unsaturated carboxylic acid copolymers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate, and unsaturated carboxylic acid copolymers such as (meth)acrylic copolymers made from ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; and polymer compounds such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyimide, polyamideimide, and carboxymethylcellulose (hereinafter also referred to as "CMC"). Depending on their physical properties, these organic binders may be dispersed or dissolved in water, or dissolved in an organic solvent such as N-methyl-2-pyrrolidone.
[0035] The content of organic binder in the negative electrode material layer of the lithium-ion secondary battery negative electrode is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, and even more preferably 3 to 15% by mass. When the organic binder content is 1% by mass or more, adhesion is improved, and the destruction of the negative electrode structure due to expansion or contraction during charging and discharging is more easily suppressed. On the other hand, when it is 30% by mass or less, the increase in electrode resistance is more easily suppressed. Within this range, the negative electrode active material has high chemical stability and can also use an aqueous binder, making it easy to handle in practical terms.
[0036] The negative electrode composition for secondary batteries may further contain conductive additives as needed. Examples of conductive additives include carbon black, graphite, acetylene black, conductive oxides, and nitrides. When the negative electrode composition for secondary batteries further contains a conductive additive, the amount is preferably in the range of 1 to 15% by mass relative to the negative electrode active material.
[0037] Examples of materials for the current collector include copper, nickel, titanium, and stainless steel. The current collector is preferably in the form of a strip, such as foil, perforated foil, or mesh. Porous materials such as porous metal (foamed metal) and carbon paper can also be used as current collectors. Methods for applying the secondary battery negative electrode composition to the current collector include, for example, metal mask printing, electrostatic coating, dip coating, spray coating, roll coating, doctor blade coating, gravure coating, and screen printing. After application, it is preferable to perform rolling treatment using a flat plate press, calender roll, etc., as needed.
[0038] Alternatively, a negative electrode material layer may be obtained by forming a paste-like composition for secondary battery negative electrodes into a sheet or pellet, and then integrating it with a current collector using a roll, press, or a combination thereof. Furthermore, a negative electrode layer can also be fabricated by adding carbon materials such as natural graphite, artificial graphite, hard carbon, or amorphous carbon such as soft carbon to the composition for the negative electrode of a secondary battery.
[0039] The negative electrode material layer formed on the current collector or the negative electrode material layer integrated with the current collector is preferably heat-treated according to the type of organic binder used. For example, when using a water-based styrene-butadiene rubber copolymer (SBR), heat treatment at 100 to 130°C is preferable, and when using an organic binder with polyimide or polyamide-imide as the main backbone, heat treatment at 150 to 450°C is preferable. This heat treatment removes solvents derived from the organic binder and promotes increased strength due to the hardening of the organic binder, thereby improving adhesion between particles and between particles and the current collector. It is preferable to perform the heat treatment under an inert gas atmosphere such as helium, argon, or nitrogen, or under a vacuum atmosphere, from the viewpoint of preventing oxidation of the current collector during the heat treatment.
[0040] Furthermore, after heat treatment, the negative electrode consisting of a negative electrode material layer formed on the current collector or a negative electrode material layer integrated with the current collector, in other words, the negative electrode of a secondary battery using this negative electrode active material, is preferably subjected to pressurization from the viewpoint of adjusting the electrode density. In such a negative electrode, the electrode density is 1 to 1.8 g / cm³. 3 Preferably, it is 1.1 to 1.7 g / cm³. 3 It is more preferable that the concentration be 1.2 to 1.6 g / cm³. 3 It is even more preferable that the electrode density is as follows: While higher electrode density tends to improve adhesion and electrode volumetric density, if it is too high, the voids in the electrode decrease, weakening the effect of suppressing Si volume expansion and potentially reducing the capacity retention rate. Therefore, an optimal range for electrode density is selected.
[0041] The secondary battery of the present invention comprises a secondary battery negative electrode having a negative electrode material layer formed using the secondary battery negative electrode composition, a positive electrode, an electrolyte, and a separator. In other words, the secondary battery of the present invention contains the negative electrode active material in the negative electrode. Preferred secondary batteries having a negative electrode containing the negative electrode active material include non-aqueous electrolyte secondary batteries and solid electrolyte secondary batteries. For example, if the secondary battery of the present invention is a wet electrolyte secondary battery, it can be constructed by arranging a positive electrode and a negative electrode containing the negative electrode active material opposite each other via a separator, and injecting an electrolyte.
[0042] The positive electrode is obtained by forming a positive electrode layer on the surface of the current collector, similar to the negative electrode. In this case, the current collector can be made of a metal or alloy such as aluminum, titanium, or stainless steel, in the form of a foil, perforated foil, mesh, or other strip.
[0043] The cathode material used in the cathode layer is not particularly limited. In the case of manufacturing lithium-ion secondary batteries, among non-aqueous electrolyte secondary batteries, examples include metal compounds, metal oxides, metal sulfides, and conductive polymers that can dope or intercalate lithium ions. Specifically, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2) and their composite oxides (LiCoxNiyMnzO2, x+y+z=1); lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 Examples include VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (where M is Co, Ni, Mn, or Fe); conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, and polyacene; and porous carbon. These may be used individually or in combination of two or more types.
[0044] As a separator, nonwoven fabrics, cloths, microporous films, or combinations thereof, mainly composed of polyolefins such as polyethylene and polypropylene can be used. However, if the positive and negative electrodes of the non-aqueous electrolyte secondary battery being manufactured are not in direct contact, a separator is not required.
[0045] As the electrolyte, a so-called organic electrolyte can be used, which is obtained by dissolving lithium salts such as LiClO4, LiPF6, LiAsF6, LiBF4, and LiSO3CF3 in one or more non-aqueous solvents such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, cyclopentanone, sulfolane, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidine-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, and ethyl acetate.
[0046] The structure of the secondary battery of the present invention is not particularly limited, but it is common to have a structure in which a positive electrode, a negative electrode, and a separator, if necessary, are wound in a flat spiral shape to form a wound electrode plate group, or these are stacked as flat plates to form a stacked electrode plate group, and these electrode plate groups are sealed in an outer casing. In the half-cell used in the embodiment of the present invention, the negative electrode is mainly composed of a negative electrode active material containing the porous silicon material of the present invention, and a simple evaluation is performed using metallic lithium as the counter electrode, in order to more clearly compare the initial discharge capacity of the porous silicon material of the present invention itself.
[0047] When the secondary battery of the present invention is a solid electrolyte secondary battery, it can be configured, for example, by comprising the positive electrode described above, the negative electrode described above containing the negative electrode active material, and a solid electrolyte interposed between the positive electrode and the negative electrode that conducts lithium ions. Examples of solid electrolytes include oxide-based lithium ion conductors such as LISICON-type ion conductors, perovskite-type ion conductors, garnet-type ion conductors, and NASICON-type ion conductors; sulfide-based lithium ion conductors such as β-Li3PS4; glass-based inorganic solid electrolytes; and thiolysicone-based solid electrolytes. These solid electrolytes may be formed into plates and placed between the positive and negative electrodes. A solid-state electrolyte secondary battery may also include a restraining member that constrains the laminate, which comprises a positive electrode, a solid electrolyte, and a negative electrode, in the direction of stacking.
[0048] The secondary battery equipped with a negative electrode using the porous silicon material of the present invention is suitably used as, for example, a paper-type battery, a button-type battery, a coin-type battery, a stacked-type battery, a cylindrical battery, a prismatic battery, and the like. The porous silicon material of the present invention is also applicable to electrochemical devices in general that use the insertion and deinsertion of lithium ions as a charge and discharge mechanism, such as hybrid capacitors and solid lithium secondary batteries. The porous silicon material of the present invention can be used not only as a negative electrode material for lithium-ion batteries, but also as a thermoelectric material, solar cell, electronic device component, filter material, and optical material.
[0049] The porous silicon material and method for producing the same according to the present invention, a negative electrode active material containing the porous silicon material of the present invention, a secondary battery negative electrode composition containing the negative electrode active material, a secondary battery negative electrode comprising a negative electrode material layer formed using the secondary battery negative electrode composition, and a secondary battery comprising the secondary battery negative electrode have been described above. However, the present invention is not limited to the configurations of the embodiments described above. For example, the porous silicon material of the present invention, the negative electrode active material containing the porous silicon material, the negative electrode composition for a secondary battery containing the negative electrode active material, the negative electrode for a secondary battery comprising a negative electrode material layer formed using the negative electrode composition for a secondary battery, and the secondary battery comprising the negative electrode for a secondary battery may each have additional configurations in the above-described embodiments, or may be replaced with any configuration that exhibits similar functions. Furthermore, the method for manufacturing the porous silicon material of the present invention may have steps for other arbitrary purposes in the above-described embodiments, or may be replaced with any steps that exhibit similar effects. [Examples]
[0050] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. Unless otherwise specified, "parts" and "%" are based on mass. In the examples, the half-cells used have a negative electrode mainly composed of a negative electrode active material containing the porous silicon material of the present invention, and a simple evaluation was performed using metallic lithium as the counter electrode. This was done to more clearly compare the initial discharge capacity of the porous silicon material of the present invention itself.
[0051] A. Examples of manufacturing porous silicon materials Example 1 (1) A mixture of silicon (wafer, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and titanium (manufactured by Kojun Chemical Laboratories, Ltd.) at 0.5 atom% was melted using a miniature arc melting furnace (Daiya Vacuum Co., Ltd. "ACM-M01") to obtain a Si-Ti alloy. Next, aluminum (pellets, manufactured by Kojun Chemical Laboratories, Ltd.) was added to obtain Al-Si-Ti alloy 1. The amounts of silicon, titanium, and aluminum used were adjusted to be 69.5 atom% for aluminum, 30 atom% for silicon, and 0.5 atom% for titanium, totaling 10 g. In other words, the metal composition ratio of Al-Si-Ti alloy 1 is 69.5 atom% for aluminum, 30 atom% for silicon, and 0.5 atom% for titanium.
[0052] (2) The obtained Al-Si-Ti alloy was melted at over 1000°C and atomized (pulverized) using nitrogen gas in a small atomizing device (manufactured by Nisshin Giken) to obtain alloy particles with a D50 of 15.0 μm. The D50 of the alloy particles was measured using a laser diffraction particle size distribution analyzer (Malvern Panalytical, "Mastersizer 3000"). (3) In a box with a nitrogen gas atmosphere, a solution of 3M hydrochloric acid with 1% by mass of isopropanol added was added to the alloy particles obtained in (2), and the reaction was carried out at 60°C for 2 hours to dealloy the mixture. The reaction mixture was filtered by suction using a 1 μm filter, washed with dehydrated ethanol, and dried under vacuum at 60°C for 10 hours to obtain porous silicon material 1.
[0053] Examples 2-14, Comparative Examples 1-3 (1) Al-Si-Ti alloys 2 to 14 and Al-Si-Ti alloys C1 to C3 were obtained in the same manner as in Example 1(1), except that the amounts (atom%) of silicon, titanium, and aluminum used were changed as shown in Table 1. (2) Next, alloy particles 2-14 and alloy particles C1-C3 having D50 as shown in Table 1 were obtained in the same manner as in Example 1(2). In Examples 8 and 14, atomization was performed using argon gas, and in Example 9, atomization was performed using helium gas. (3) Furthermore, porous silicon materials 2-14 and porous silicon materials C1-C3 were obtained by performing the same procedure as in Example 1(3). The reaction time for dealloying was changed from 2 hours to 30 minutes in Examples 4 and 11, from 2 hours to 6 hours in Example 10, and from 2 hours to 4 hours in Example 13. In addition, in Examples 5, 12, and 13, a solution of 3M hydrochloric acid with a mixture of ethanol and methanol at a concentration of 1% by mass was used instead of a solution of 3M hydrochloric acid with a concentration of 1% by mass of isopropanol.
[0054] B. Evaluation of porous silicon materials The following physical properties were measured for the porous silicon materials obtained in each example and comparative example. The results are summarized in Table 1. (1) Average particle size (D50) The measurement was performed using a laser diffraction particle size distribution analyzer (Malvern Panalytical, Mastersizer 3000).
[0055] (2) Porosity Using a fully automated pore size analyzer (Quanta Chrome's "pore Master 60-GT"), the sample was placed in a sample cell, and the pore size distribution was determined within the measurement range of 400 μm to 0.0036 μm. The porosity was then calculated as follows. Porosity=100×P / R P: Pore volume = Cumulative pore volume calculated by pore distribution measurement × Mass of sample R: Bulk volume = Total cell volume - Cell volume excluding sample
[0056] (3) Average support diameter A porous silicon material was fixed onto copper foil, and cross-sections cut using a cross-section polisher (registered trademark; JEOL Ltd. "IB-19520CCP") were observed at arbitrary magnifications (5000 to 50000x) using a scanning electron microscope (SEM (SEM): JEOL Ltd. "FEM-7900F"). The SEM images were analyzed using image analysis software (Image J) to measure the short axis of 100 arbitrary silicon domains, and the average value was calculated to determine the average column diameter.
[0057] (4) Element mass ratio (O / Si) A porous silicon material was pressed onto a flattened Sn plate at 25 kPa, and the masses of each element (O, Si, Al, Ti) in the porous silicon material were measured using an energy-dispersive X-ray analyzer (EDS, JEOL Ltd. "JED-2300") attached to the aforementioned scanning electron microscope at an acceleration voltage of 25 kV. The elemental mass ratio A (O / Si) of Si to O and the elemental mass ratio E of Si to Al were then calculated.
[0058] (5) Specific surface area The specific surface area was measured using a specific surface area measuring device (Microtrac-Bel "BELsorp miniX"), and the BET specific surface area B was calculated by BET method analysis using nitrogen gas adsorption measurement. Using the elemental mass ratio A of Si and O calculated in (4) above, and the BET specific surface area B, Y was determined based on equation (2).
[0059] (6) Crystallization peak and heat quantity Using a differential scanning calorimeter (DSC: Hitachi High-Tech Science Corporation "X-DSC7000"), measurements were taken under the following conditions: starting temperature 30°C, heating rate 20°C / min, target temperature 460°C, nitrogen atmosphere, and flow rate 50 ml / min. The measurement results for commercially available crystalline Si powder were used as a blank (reference), and the calorific value was determined by identifying the crystallization peak as the analytically significant difference.
[0060] (7) Crystallite size The crystallite size of the Si(111) plane was calculated using the fundamental parameter (FP) method, based on measurements performed with a wide-angle X-ray diffraction (XRD) instrument (Rigaku Corporation's "Ultima IV"). The measurement conditions are as follows: Cu / Kα line: 40kV / 40mA Scan speed: 2° / min Step: 0.02° Scanning range: 5° to 70°
[0061] C. Evaluation of battery characteristics in half-cells of porous silicon material A slurry was prepared by mixing 6.9 parts by mass of the porous silicon material obtained in each example and comparative example with 1 part by mass of acetylene black and 0.1 parts by mass of carbon nanotubes as conductive additives, and a mixture of 0.25 parts by mass of CMC and 0.75 parts by mass of SBR (total 1 part by mass) as a binder, and stirring for 10 minutes in a rotation-orbit mixer (Thinky Co., Ltd. "Awatori Rentaro"). The obtained slurry was deposited as a film on a copper foil with a thickness of 20 μm. After drying under reduced pressure at 110°C, it was punched out into a circular shape with a diameter of 14 mm, and weighed approximately 1.0 g / cm². 3 The negative electrode was obtained as a thin film by pressing it using a tablet molding machine. The thickness of the obtained negative electrode was measured at five points using a thickness gauge (Nikon MF-501), and the average value was defined as L0. Next, in a dry room with a moisture dew point of -40°C or lower, a Li metal foil was used as the counter electrode, and the negative electrode obtained above was placed opposite it via a polypropylene separator (25 μm thick). A non-aqueous electrolyte solution, in which lithium hexafluoride phosphate was dissolved at a concentration of 1 mol / L in a mixture of ethylene carbonate and diethyl carbonate in a 1:1 volume ratio, was adsorbed onto the Li metal foil, and a coin-type lithium-ion battery (CR2032 type) was fabricated as a half-cell.
[0062] Using a secondary battery charge / discharge test apparatus (manufactured by Hokuto Denko Co., Ltd.), the charge / discharge characteristics of the fabricated half-cells were evaluated at 25°C, with a cutoff voltage range of 0.005 to 1.5V, and charge / discharge rates of 0.1C (1 to 3 cycles) and 0.2C (4 cycles and beyond), under constant current / constant voltage charging / constant current discharging conditions. The open circuit state was maintained for 30 minutes during each charge / discharge switching. The initial discharge capacity (mAh / g) and cycle characteristics after 10 charge / discharge cycles are shown in Table 1. Furthermore, the coin-type lithium-ion battery described above was disassembled in its initial fully charged state, the negative electrode was removed, washed with dimethyl carbonate, and air-dried. The thickness of this negative electrode was measured at five points using a thickness gauge, and the average value was taken as L1. The expansion rate of the negative electrode was calculated using the following formula. The results are shown in Table 1. Expansion rate (%) = 100 × L1 / L0
[0063] [Table 1]
[0064] D. Evaluation of battery characteristics in all-solid-state batteries using porous silicon materials. Example 15 In Example 3, 60 parts by mass of the porous silicon material 3 was mixed with 35 parts by mass of β-Li3PS4 (manufactured by NEI Corporation) as a solid electrolyte and 5 parts by mass of VGCF (Vapor Grown Carbon Fiber; manufactured by Resonaq Corporation) as a conductive material, while being crushed in a mortar to obtain a negative electrode composite material. The obtained negative electrode composite material was pressed at 20 MPa to produce a negative electrode composite material layer. On the other hand, a solid electrolytic layer was fabricated by pressing the above solid electrolyte at 30 MPa. Furthermore, by pressing Li foil (manufactured by Honjo Metal Co., Ltd.) and In foil (manufactured by Nihon Handa Co., Ltd.) at 30 MPa, a Li-In alloy foil was obtained to serve as the positive electrode. Then, the negative electrode mixture layer, solid electrolytic layer, and Li-In alloy foil prepared as described above are stacked in this order to create a surface pressure of 5 t / cm². 2 All-solid-state batteries for evaluation were fabricated by tightly bonding the layers together, sealing them with tabbed laminate, and pressing them at 60 MPa to create a laminated structure. Using a secondary battery charge / discharge test apparatus (manufactured by Hokuto Denko Co., Ltd.), the charge / discharge characteristics (cycle characteristics) of the fabricated all-solid-state battery were evaluated at 45°C under the conditions of initial constant-current / constant-voltage charging at 0.3mA down to -0.57V, followed by constant-current discharge at 0.3mA down to 0.88V. The results are shown in Table 2.
[0065] Example 16 In Example 15, an all-solid-state battery was fabricated in the same manner as in Example 15, except that porous silicon material 6 obtained in Example 6 was used instead of porous silicon material 3, and the cycle characteristics were evaluated. The results are shown in Table 2. Comparative Example 4 In Example 15, an all-solid-state battery was fabricated in the same manner as in Example 15, except that porous silicon material C3 obtained in Comparative Example 3 was used instead of porous silicon material 3, and the cycle characteristics were evaluated. The results are shown in Table 2.
[0066] [Table 2]
[0067] The results in Tables 1 and 2 show that the negative electrode active material containing the porous silicon material of the present invention can suppress the expansion and contraction of the negative electrode containing such negative electrode active material, and exhibits excellent initial discharge capacity and cycle characteristics. Furthermore, secondary batteries containing the porous silicon material of the present invention as a negative electrode active material exhibit excellent battery characteristics such as charge and discharge characteristics. [Industrial applicability]
[0068] The negative electrode formed using the negative electrode active material containing the porous silicon material of the present invention suppresses expansion and contraction associated with repeated charging and discharging, and exhibits excellent initial discharge capacity and cycle characteristics. Secondary batteries having such a negative electrode have excellent battery characteristics such as charge and discharge characteristics, and can be effectively used in portable electronic devices, for example, as paper type batteries, button type batteries, coin type batteries, stacked type batteries, cylindrical batteries, prismatic batteries, etc. The negative electrode active material containing the porous silicon material of the present invention can also be applied to electrochemical devices in general that use the insertion and deinsertion of lithium ions as a charge and discharge mechanism, such as hybrid capacitors and solid lithium secondary batteries.
Claims
1. A porous silicon material having a lamellar or columnar structure with an average column diameter of 1 nm to 100 nm in silicon domains, and a porosity Q calculated by the following formula (1) being greater than 40% and less than 80%. Q (%) = 100 × P / (V + P) ... (1) P: Pore volume of porous silicon material V: Volume of porous silicon material
2. The porous silicon material according to claim 1, comprising at least a portion of an amorphous silicon component.
3. The porous silicon material according to claim 1, wherein when the elemental mass ratio of silicon (Si) to oxygen (O) (O / Si) is A, and the BET specific surface area measured by nitrogen gas adsorption is B, the value Y calculated by the following formula (2) is greater than 0 and less than 0.
2. Y=100×A / B...(2)
4. The porous silicon material according to claim 1, having one or more crystallization peaks between 350°C and 450°C in DSC (differential scanning calorimetry) analysis.
5. The porous silicon material according to claim 1, wherein the crystallite size of the Si(111) plane, calculated by the fundamental parameter (FP) method using X-ray diffraction analysis, is 130 nm or less.
6. A porous silicon material according to claim 1, formed using an alloy shown in formula (3) below as a raw material. AlxSiyTiz...(3) (In the formula, x is between 45 atom% and less than 75 atom%, y is between 25 atom% and 45 atom%, and z is greater than 0 atom% and less than 5 atom%.)
7. The porous silicon material according to claim 6, wherein the elemental mass ratio E of Si to Al is greater than 0 and less than 0.
04.
8. The porous silicon material according to claim 6, which does not contain an Al-Si-Ti compound.
9. A method for producing a porous silicon material according to any one of claims 1 to 8, comprising the following steps. (i) Process for producing Si-Ti alloy (ii) A step of adding aluminum metal to the Si-Ti alloy obtained in step (i) above to produce an alloy represented by the following formula (3). AlxSiyTiz...(3) (In the formula, x is between 45 atom% and less than 75 atom%, y is between 25 atom% and 45 atom%, and z is greater than 0 atom% and less than 5 atom%.) (iii) A step of atomizing the alloy represented by formula (3) obtained in step (ii) using a gas atomizer to obtain alloy particles. (iv) A step to obtain a porous silicon material by dealloying the alloy particles obtained in step (iii) with an acid or alkali containing alcohol.
10. The method for producing a porous silicon material according to claim 9, wherein the average particle size (D50) of the alloy particles obtained in step (iii) is in the range of more than 0.1 μm and less than 20 μm.
11. A negative electrode active material comprising the porous silicon material described in any one of claims 1 to 8.
12. A composition for a secondary battery negative electrode, comprising the negative electrode active material described in claim 11.
13. A secondary battery negative electrode comprising a negative electrode material layer formed using the secondary battery negative electrode composition described in claim 12.
14. A secondary battery comprising a negative electrode, a positive electrode, an electrolyte, and a separator as described in claim 13.
Citation Information
Patent Citations
Active material for negative electrode
JP2016051622A
Manufacturing method of porous silicon grain, manufacturing method of electrode for electricity storage device, manufacturing method of whole solid lithium ion secondary battery, porous silicon grain, electrode for electricity storage device, and whole solid lithium ion secondary battery
JP2021123517A
Method for producing porous silicon material, porous silicon material and power storage device
JP2023068494A
Porous amorphous silicon, method for producing porous amorphous silicon, and secondary battery
WO2020194794A1